Effects of Nonthermal Radiofrequency Stimulation on Neuronal Activity and Neural Circuit in Mice - Yanhui Hao; Weiqi Liu; Yujie Liu; Ying Liu; Zhengtao Xu; Yumeng Ye; Hongmei Zhou; Hua Deng; Hongyan Zuo; Hong Yang; Yang Li (Advanced Science, 2023)
Abstract Whether the nonthermal effects of radiofrequency radiation (RFR) exist and how nonthermal RFR acts on the nervous system are unknown. An animal model of spatial memory impairment is established by exposing mice to 2856‐MHz RFR in the range of thermal noise (≤1 °C). Glutamate release in the dorsal hippocampus (dHPC) CA1 region is not significantly changed after radiofrequency exposure, whereas dopamine release is reduced. Importantly, RFR enhances glutamatergic CA1 pyramidal neuron calcium activity by nonthermal mechanisms, which recover to the basal level with RFR termination. Furthermore, suppressed dHPC dopamine release induced by radiofrequency exposure is due to decreased density of dopaminergic projections from the locus coeruleus to dHPC, and artificial activation of dopamine axon terminals or D1 receptors in dHPC CA1 improve memory damage in mice exposed to RFR. These findings indicate that nonthermal radiofrequency stimulation modulates ongoing neuronal activity and affects nervous system function at the neural circuit level.